Left lateralized P300 amplitude deficit in schizophrenic patients depends on pitch disparity - Weisbrod, Matthias; Winkler, Sabine; Maier, Sabine; Hill, Holger; Thomas, Christine; Spitzer, Manfred (Biological psychiatry, 1997)
The general reduction of P300 amplitude in response to auditory oddball stimuli is one of the most consistently replicated biological observations in schizophrenic patients. Several groups have reported a P300 asymmetry in schizophrenic patients, others have not been able to replicate this finding. In order to clarify this issue, we examined the effect of stimulus discriminability on P300 amplitude distribution in schizophrenic patients and in age-matched normal control subjects, using two different auditory oddball paradigms. The detection of the target tone was either simple or difficult, due to manipulation of pitch disparity. The P300 amplitude was comparatively smaller in the schizophrenic patient group compared to the healthy controls and in the difficult task compared to the simple. The schizophrenic patients showed a specific P300 amplitude reduction over left temporal electrode sites when the simple paradigm was used. The difficult paradigm did not elicit asymmetrical P300 amplitudes in schizophrenic patients.